Exploring the Integration of Cultural Tourism and Sports: A Development Path Based on Dialogue Theory - Jingya Yue; Yujie Su, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The sustained vitality of cultural tourism integration lies in fostering a deep connection between the supply and consumer sides, enhancing consumer engagement, and creating experiences that resonate deeply with participants. Applying Bakhtin's dialogue theory, this paper suggests that the development of cultural tourism and sports integration should emphasize multi-dimensional dialogue between products and consumer groups. This approach requires addressing various levels of human needs, including ego, self, and superego demands, while moving beyond simple aggregation of industries and products to create meaningful interactions. The integration process must balance the relationships between elements, ensuring that the products provided are not only the outcome of dialogue between organizers and consumers but also facilitate continuous reproduction and re-creation through ongoing interaction. Dialogue, as both a mode of production and consumption, allows for dynamic exchanges that can evolve over time. In the context of sports tourism, this dialogue fosters the creation of high-quality, interactive experiences that enhance consumer engagement and sustain industry vitality. By integrating cultural and sports tourism through dialogic frameworks, this approach provides a pathway to develop innovative, consumer-driven experiences that promote physical activity, cultural appreciation, and economic sustainability.